(untitled) (Research, Society and Development, 2018)
The Environmental Education has long been becoming an important theme, being necessary the understanding on the concepts and trends, national and international. In this way we bring here a narrative revision, built from the mapping of articles, books and research, based on national and international periodicals, related to the area of interest, studying them and then summarizing, confronting in the aspects related to concepts, opinions, paradigms and visions. The intention is to provide an up-to-date look at the subject, not necessarily exhausting, but to provoke the reflection on the tendencies that lead to the best relation of the human being to the environment. Finally we draw a correlation between Environmental Education and Education for Sustainable Development.